Porto_Alegre una biografia territoriale - Giovanni, Allegretti (Strumenti per la didattica e la ricerca, 2005)
The experience of Porto Alegre has and continues to represent for the entire world a benchmark standard in terms of the participation of citizens in territorial government. Dwelling principally on the technical-instrumental aspects of its extraordinary parable, this book attempts to reconstruct, over and above any evaluation, a biography of the territory and the communities in play, telling the story of how a site on the planet can become a planetary site of participatory democracy.